KEPRIBADIAN TOKOH DALAM MENGHADAPI KONFLIK PADA NOVEL PESAN DARI SAMBU KARYA TASMI,P.S. - Hasianthy Hutauruk, Sonia Nelly; Faizah, Hasnah; Syafrial, Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This Research Entitled Personality Of Character To Facing The Conflict On “Pesan Dari Sambu”’s Novel By Tasmi,P.S. . The Purpose Of This Research Is To Describe The Personality of character on “Pesan Dari Sambu”’s novel by Tasmi P.S, as id, ego and super ego aspect. The Data of this research is words and sentences of “Pesan Dari Sambu”’s Novel By Tasmi,P.S. The Results of this research is character personality based on id, ego, super ego aspect. Id’s personality describes the attitude of primitive instinct and prioritizes comfort and avoids pain. Ego’s personality describes highlights the nature that people around them want to acknowledge. Super egos’s personality describes behave in accordance with the teachings of parents and religion.Keyword : Personality, Caracter and Conflict